Neutrophil hypersegmentation in children receiving angiotensin converting enzyme inhibitors - Okutan, Vedat; Kürekçi, A. Emin; Sarıcı, S. Ümit; Atay, A. Avni; Yozgat, Yılmaz; Azık, Fatih; Lenk, M. Koray; Özcan, Okan (The Turkish Journal of Pediatrics, 2008)
Captopril and enalapril are the most commonly used angiotensin converting enzyme inhibitors in several cardiac diseases in children. On the other hand, the intrinsic renin-angiotensin system in the bone marrow might affect the growth of hematopoietic colonies and cellular production, proliferation and differentiation in physiological and pathological states. Starting with the hypothesis that inhibition of the renin-angiotensin system may have some effects on the hematopoietic system, including morphological changes within the granulocytes, we thus aimed to investigate prospectively whether the use of angiotensin converting enzyme inhibitors has any effect on the morphology, and especially segmentation, of neutrophils in peripheral blood. A total of 40 children with various heart diseases receiving either of two angiotensin converting enzyme inhibitors (captopril or enalapril) aged between 2 to 16 years were enrolled, and 40 healthy age- and sex-matched children were enrolled as controls. Complete blood count, peripheral blood smear, liver and renal function tests, and measurement of serum alkaline phosphatase, ferritin, vitamin B12 and folate levels were performed in all cases. Peripheral blood smears were viewed by two pediatric hematologists in a blinded manner. Neutrophil hypersegmentation was described as presence of five or more neutrophils with five well-separated lobes or at least one neutrophil with six or more lobes among 100 segmented neutrophils. The number of patients with neutrophil hypersegmentation in the study group was significantly higher than in the control group, and the mean lobe count in the study group was significantly higher than in the control group. Neutrophil hypersegmentation, as detected in patients using angiotensin converting enzyme inhibitors in the present study, has not been reported previously. Further studies aiming to explain the pathophysiological mechanism(s) underlying neutrophil hypersegmentation in patients receiving angiotensin converting enzyme inhibitors are needed.